Prevalence and Predictors of Intimate Partner Violence Among Married Women in Egypt - Yaya, Sanni (Journal of interpersonal violence, 2021)
Intimate partner violence (IPV) among married women of childbearing age can significantly enhance their risk of adverse health outcomes such as injury and disability, depression and anxiety, unwanted pregnancies, premature labor, complications with delivery, and perinatal and neonatal mortality. The objective of this study was to examine the prevalence and individual and societal factors associated with IPV among Egyptian women. Cross-sectional data on 12,205 ever-married women between the ages of 15 to 49 years were collected from the Egypt Demographic and Health Survey (EDHS). Data from the 2005 and 2014 EDHS were pooled and analyzed. Self-reported responses on violence by husbands were classified into physical, sexual, and emotional violence. The factors of association were quantified using logistic regression methods. The prevalence of experiencing any form of violence among ever-married women in Egypt was 29.4%. Overall, women reported experiencing physical, emotional, and sexual violence at 26.7%, 17.8%, and 4.6%, respectively. Women in the age group of 25 to 29 years had the highest odds (odds ratio [OR] = 1.539, 95% confidence interval [CI] = [1.327, 1.785]) of suffering from any form of IPV. Women residing in urban areas (OR = 1.149, 95% CI = [1.046, 1.262]), having only a primary-level education (OR = 1.756, 95% CI = [1.543, 1.999]), being followers of Islam (OR = 1.713, 95% CI = [1.379, 2.126]), and having husbands with no education (OR = 1.422, 95% CI = [1.263, 1.601]) reported having higher odds of experiencing any form of IPV. Nearly one third of married women of childbearing age are exposed to IPV of any form in Egypt. IPV intervention programs should pay special attention to the socioeconomically vulnerable segments of the population and promote educational status among men and women to curb the occurrence of IPV.